Sustainable Finance: A Bibliometric Analysis of Green Finance and its Role in Global Markets - Loso Judijanto; Nanang Qosim; Syamsulbahri Syamsulbahri; Eva Yuniarti Utami; Chairil Afandy (West Science Business and Management, 2024)
This study conducts a comprehensive bibliometric analysis to map the evolution and scope of sustainable finance research from 2000 to 2024. Utilizing data sourced from Scopus, the analysis identifies major trends, themes, and contributions within the field, emphasizing the increasing integration of sustainability into financial practices. Key findings reveal a dramatic rise in publications over recent years, underscoring the growing academic and practical interest in sustainable finance. The research network analysis highlights significant global collaboration and the central role of technological innovations like fintech and artificial intelligence in advancing sustainable financial practices. The study also explores regional dynamics, showing robust contributions from both developed and emerging economies. Overall, this analysis provides crucial insights into how sustainable finance can be strategically advanced to meet global sustainability goals, offering directions for policy, practice, and future research.